Pengaruh Air Rebusan Daun Sambiloto Terhadap Penurunan Kadar Kolesterol : The Effect of Boiling Water on Sambiloto Leaves on Reducing Cholesterol Levels - Vicky Fauzan Aliansah (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Andrographis paniculata, is a medicinal plant that is also very easy to breed. This plant contains many active chemical constituents which exhibit definite pharmacological effects. This can be easily predicted from the findings of the bitter leaf article, which has anti-inflammatory, anticancer, antidiabetic, antiangiogenic, antimalarial, and antimicrobial activities. Methods: This study is quantitative, using a quasi-experiment with a pres-post group control design. This study applies the observation method for the implementation of data collection from respondents' cholesterol levels. The description of the frequency of lowering cholesterol levels before giving the boiled water of bitter leaves is still partly high by 50% or 10 people. Results: The results showed that there was an effect of giving boiled water of bitter leaves to decrease cholesterol levels with a p-value = 0.347 (α < 0.05). Discussion: The results showed that there was an effect of boiled water from bitter leaves (Andrographis paniculata) on reducing cholesterol levels in the area of RW 07, Cinere District, Depok City.